Multifaith Relationships and Civilization-Building in India’s Muslim States and Societies - Arshad Islam, Islam (The world Muslim Communities Council, 2022)
Islam arrived in India long before the dawn of Muslim political power, and even in its pre-political stage it made a significant impact on the lives of local people. Traders of the Arabian maritime civilization became well known for their fairness and righteousness among the ports of India and beyond, long before the region of Sindh became a gateway to Islamic political domination in north-west India. Throughout the Subcontinent the sociocultural history of the region has always been characterized by an incredibly multicultural society, divided into various groups belonging to diverse castes and creeds.1